Plasmodium falciparum: sequence diversity and antibody recognition of the Merozoite surface protein-2 (MSP-2) in Brazilian Amazonia - Tonon, A. P.; Hoffmann, EHE; da Silveira, L. A.; Ribeiroa, A. G.; Goncalves, CRD; Ribolla, PEM; Wunderlich, G.; Ferreira, M. U. (Elsevier B.V., 2004)
The merozoite surface protein-2 (MSP-2) of Plasmodium falciparum comprises repeats flanked by dimorphic domains defining the allelic families FC27 and IC1. Here, we examined sequence diversity at the msp-2 locus in Brazil and its impact on MSP-2 antibody recognition by local patients. Only 25 unique partial sequences of msp-2 were found in 61 isolates examined. The finding of identical msp-2 sequences in unrelated parasites, collected 6-13 years apart, suggests that no major directional selection is exerted by variant-specific immunity in this malaria-endemic area. To examine antibody cross-reactivity, recombinant polypeptides derived from locally prevalent and foreign MSP-2 variants were used in ELISA. Foreign IC1-type variants, such as 3D7 (currently tested for human vaccination), were less frequently recognized than FC27-type and local IC1-type variants. Antibodies discriminated between local and foreign IC1-type variants, but cross-recognized structurally different local IC1-type variants. The use of evolutionary models of MSP-2 is suggested to design vaccines that minimize differences between local parasites and vaccine antigens. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: protozoa; malaria parasites; MSP-2; antigenic diversity; vaccine